Ethical Leadership: A Study of Integrity in Organizations in the Middle East - Randeree, K (Victoria University Business and Law, 2008)
A justice framework can be used to understand how individuals within organisations respond to a variety of human resources practices and also can be used prescriptively in designing the procedures and enactment of human resource practices. The principles of justice can be applied in order to understand the consequences of any human resource practice. This paper examines the impact of the perception organisational justice on job satisfaction of unskilled workers of the city of Dubai in the United Arab Emirates (UAE). The key findings of the research revealed Dubai as having the largest proportion of expatriate workers globally and that these employees present a high level of grievance towards their employers. Major issues highlighted by the survey include pay, workload, job responsibilities, bias and employer injustice.